A Study of Substituted Aliphatic Sulphides on the Corrosion Behaviour of Zinc in Ammonium Chloride Solution. Issue 1 (2007) - Venckatesh, R.; Shabudeen, P. S. Syed; Gopal, S.
Abstract : Sulphur containing organic compounds decreases the corrosion rate by increasing the hydrogen over potential on zinc metal due to their electron donating groups. Their inhibiting effect was found to be associated with their adsorption on the active centers of the metal. The inhibition efficiencies of some aliphatic sulphides in ammonium chloride solution have been studied by weight loss studies, polarization and impedance measurements. The effect of substituent groups is correlated with their inhibition performance. These studies due to their relevance in Zn-Manganese dry batteries assume their importance.